Beneficial effects of emodin and curcumin supplementation on antioxidant defence response, inflammatory response and intestinal barrier of Pengze crucian carp (Carassius auratus var. Pengze). (1st September 2020) - Yang, Gang; Yu, Ruihe; Qiu, Huimin; Wu, Huadong; Yan, Quangen; Chen, Wenjing; Ding, Liyun; Kumar, Vikas; Wen, Chungen; Peng, Mo
Abstract: The object of this work is to investigate the effects of emodin and curcumin on Pengze crucian carp. Fish was, respectively, fed Control diet and supplementation of 50 mg/kg emodin (EM group) and curcumin (CU group) with 4 repetitions each group (20 fish per cage). Our results indicated that the growth was unaffected by diets, whilst whole‐body lipid content was detected to remarkably decrease in EM group. Two additives exerted positive impacts on antioxidant system through elevation of antioxidant enzymes activities and antioxidants content. The improvement of intestinal antioxidant property appeared to be associated with up‐regulating expression of antioxidant genes through nuclear factor erythroid 2‐related factor 2 (Nrf2) activation. Moreover, intestinal inflammatory response was suppressed in EM and CU groups through inhibition of Toll‐like 4 receptor (TLR4) signalling pathway and pro‐inflammatory cytokine genes expression, and it may be related to the regulation of antioxidant system and overexpression of interleukin‐10. Afterwards, intestinal barrier function was enhanced in EM and CU groups by inducing the expression of tight junction protein genes. These results revealed that emodin and curcumin exerted positive benefits on the health of Pengze crucian carp by enhancing antioxidant capacity, suppressing inflammatory response and improving intestinal barrier function.